PEMANFAATAN APLIKASI JIBAS (JARINGAN INFORMASI BERSAMA ANTAR SEKOLAH) DALAM ADMINISTRASI AKADEMIK SEKOLAH DI SMK NEGERI 2 TAKALAR - Mujahida Azzahra; Irmawati; Ahlun Ansar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the utilization of the JIBAS (Joint Inter-School Information Network) application in school academic administration, as well as the supporting and inhibiting factors, at SMK Negeri 2 Takalar. The study employs a qualitative approach with a descriptive research design. Data collection was conducted through observation, interviews, and documentation, involving the school principal, head of administration, teachers, and school operators. Data analysis involved data reduction, data presentation, and conclusion drawing, while data validity was verified using source and method triangulation. The results indicate that the utilization of JIBAS at SMK Negeri 2 Takalar encompasses more structured and accurate student data management; curriculum and scheduling management that helps minimize scheduling conflicts between teachers and classes; academic communication via the InfoGuru (Teacher Info) and InfoSiswa (Student Info) features, which accelerate information delivery to students and parents; grade and report card management that enhances assessment transparency; and more efficient student and teacher attendance tracking that serves as a basis for disciplinary guidance. Supporting factors for the implementation of JIBAS include the availability of digital facilities and infrastructure, as well as school policies promoting administrative digitalization. Conversely, inhibiting factors include limited digital literacy among some staff members, the need for continuous training, and technical constraints regarding system maintenance. The study concludes that the implementation of JIBAS has a positive impact on the efficiency, transparency, and accountability of school administration. However, optimizing its use still requires policy support, the enhancement of human resource competencies, and the strengthening of digital infrastructure.